Peningkatan Kompetensi Pedagogik Mahasiswa Melalui Penerapan Metode Peer Teaching Dalam Mata Kuliah Microteaching - Muhammad Faisal Lutfi Amri Amri; Nur Sakinah Aries; A. Nurmutmainnah (Indonesian Journal of Physical Activity, 2026)
This study aimed to examine the effectiveness of the peer teaching method in enhancing the pedagogical competence of pre-service teachers enrolled in the Microteaching course in the Physical Education Study Program at Universitas Negeri Gorontalo. The study employed a Classroom Action Research (CAR) design implemented in two cycles, consisting of the stages of planning, action, observation, and reflection. The participants were 22 undergraduate students taking the Microteaching course during the 2025/2026 academic year. Data were collected through classroom observations and assessments of students' pedagogical competence using structured evaluation rubrics developed based on teaching competency indicators. The findings indicated that the implementation of the peer teaching method significantly improved students' pedagogical competence. The percentage of students who achieved the minimum mastery criterion (≥80) increased from 36.4% in Cycle I to 81.8% in Cycle II. During the first cycle, most students did not meet the expected competency standards, as only 36.4% achieved scores above the established mastery criterion. This outcome was primarily attributed to students' limited ability to apply fundamental teaching skills effectively. Following instructional improvements and a more systematic implementation of the peer teaching method in the second cycle, students demonstrated substantial progress in classroom participation, active engagement, self-confidence, and their ability to design and implement instructional activities. Consequently, the proportion of students who achieved the predetermined mastery criterion increased considerably, while the number of students who failed to meet the expected standard declined. These findings suggest that the peer teaching method is an effective instructional strategy for developing the pedagogical competence of pre-service physical education teachers. Therefore, this approach can be considered an innovative learning strategy for improving the quality of Microteaching instruction and preparing future teachers who are professionally competent, reflective, and capable of meeting the challenges of 21st-century education.